Viability Test of Stored Corn Seeds Based on The Relationship Between Concentration of Inorganic exudates and Electrical Conductivity of Soaking Water - T. S. Endang; P. Yudono; D. Indradewa (Jurnal Ilmu Pertanian, 2001)
-